2023
DOI: 10.1039/d2nr04840j
|View full text |Cite
|
Sign up to set email alerts
|

Promising ultra-short channel transistors based on OM2S (M = Ga, In) monolayers for high performance and low power consumption

Abstract: Two-dimensional (2D) semiconductors are hoping to overcome the short channel effect and continue Moore's law. However, the 2D materials-based ultra-short channel devices still face the challenge of simultaneously achieving high-performance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…34 Studies have shown that monolayer OM 2 S has great application prospects in ultrashort scale devices. 28 The above results indicate that monolayer films M 2 OS have shown good stability, high electron mobility, and suitable band gaps, making them promising candidates for further extending Moore's Law, and are predicted to have wide applications in optoelectronics and nanoelectronics. The vertical van der Waals heterostructure (vdWH) is currently a very popular method of constructing devices.…”
Section: ■ Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…34 Studies have shown that monolayer OM 2 S has great application prospects in ultrashort scale devices. 28 The above results indicate that monolayer films M 2 OS have shown good stability, high electron mobility, and suitable band gaps, making them promising candidates for further extending Moore's Law, and are predicted to have wide applications in optoelectronics and nanoelectronics. The vertical van der Waals heterostructure (vdWH) is currently a very popular method of constructing devices.…”
Section: ■ Introductionmentioning
confidence: 84%
“…The optimized lattice constants of monolayer Ga 2 OS and In 2 OS are a = b = 3.367 and 3.674 Å, respectively, which are consistent with previous research results. 28,29 The projected band structures of monolayers Ga 2 OS and In 2 OS are investigated, as presented in Figure 1b,c. The results show that monolayer Ga 2 OS is a direct band gap semiconductor with a band gap of 1.39 eV, where the conduction band maximum (CBM) is mainly contributed by the Ga atom and the valence band minimum (VBM) is mainly contributed by the S atom.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is important to improve the OER performance of spinel sulfide by activating active sites and accelerating electron transmission. Many effective strategies have been carried out to enhance catalytic performance, such as dopant insertion, 5,6 defect 7,8 and heterojunction construction, [9][10][11] and surface interface regulation. 12,13 The strategy of element doping has been widely used to adjust the structure to obtain more active sites and improve electrical conductivity.…”
mentioning
confidence: 99%